Locked up in the Science Laboratory: A smooth transition from class-room to escape-room - Nikos Bessas; Eleni Tzanaki; Denis Vavougios; Vassilis P. Plagianakos (Social Sciences and Humanities Open)
We are at a time when students seem to be losing interest in school. This decline is particularly noticeable in Physics and Mathematics. Student performance and grades are in decline and teachers have begun to look for ways through their teaching to regain the lost glory of the school and make it an important contributor to society in an ever-changing environment. The aim of the educational community is to attract the student at the last desk by involving him or her in the teaching process through active participation. This study aims to integrate escape rooms, in the context of the Physics and Mathematics Curriculum, into the learning process and to introduce game-based learning activities as an alternative form of teaching. For this purpose, during the 2023-24 school year, an educational escape room was created and implemented at a junior high school in Athens, Greece. A total of 9 students participated in the escape room, while a total of 60 students were involved in this activity. After completing the process, all the students filled out a questionnaire regarding their experience and the extent to which they accepted this method as a teaching tool. At the end, a statistical analysis of the questionnaire and a discussion on the emergence of escape rooms as suitable educational tools in the teaching process is followed.